Doctor-patient interactions in the age of AI: navigating innovation and expertise - Hryciw, Brett N.; Fortin, Zanna; Ghossein, Jamie; Kyeremanteng, Kwadwo (Frontiers in Medicine, 2023)
The integration of artificial intelligence (AI) in healthcare has the capacity to transform medical practice. Despite its revolutionary potential, the influence of AI may affect the physician-patient interaction and presents ethical challenges that will need to be carefully considered. This article discusses how patients may interact with this technology, considers how emerging technologies may alter the dynamics of the physician-patient relationship, and reviews some of the limitations that continue to exist. We identify potential challenges that may arise with the integration of AI into medical settings and propose solutions to help mitigate these issues.